Ciprofloxacin-resistant E. coli community-acquired upper urinary tract infection: associated characteristics in patients of a national hospital in Peru - Montañez Valverde, Raúl A. (2015)
Introduction. Urinary tract infections (UTI) represent a common health problem. In Peru Escherichia coli resistance rates to ciprofloxacin vary from 31% to 69.8%. Objectives. To determine the frequency and characteristics associated with community-acquired ciprofloxacinresistant E. coli upper urinary tract infection (cUTI). Design. Cross-sectional study. Setting. Emergency Department, Edgardo Rebagliati Martins Hospital, Lima, Peru. Participants. Patients diagnosed with cUTI in 2010. Interventions. Medical records of patients with cUTI and urine cultures positive for E. coli were reviewed. Descriptive analysis (mean, frequency) and bivariate analysis (chi-square test or Fisher test) were used with p <0.05 significance. Main outcomes measures. Sociodemographic variables, clinical presentation, comorbidities and resistance to other antibiotics. Results. Eighty-one patients with cUTI were included, mean age 65 (± 17.4) years; 57 (70.4%) patients had ciprofloxacin-resistant E. coli infection associated (p  <0.05) with resistance to cotrimoxazole, cephalosporins, aminoglycosides and expanded spectrum beta-lactamase (ESBL)-producing organisms. In these patients prior use of cephalosporins and quinolones was more frequent (p> 0.05) as well as neurological, gastrointestinal and renal comorbidities. Conclusions. Communityacquired ciprofloxacin-resistant E. coli upper urinary tract infection was more frequent than in previous studies and associated with resistance to cotrimoxazole, cephalosporins, aminoglycosides and ESBL- producing organisms.